1994
DOI: 10.1063/1.112455
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the electron Hall mobility in 4H, 6H, and 15R silicon carbide

Abstract: Hall effect measurements in a Hall-bar configuration are performed on nitrogen-doped n-type bulk 4H, 6H, and 15R SiC single crystals cut into small parallelepipeds with their longest edges either parallel or perpendicular to the ĉ axis. In the temperature range investigated (40–700 K), an anisotropy of the electron Hall mobility is observed in all three polytypes. While the mobility perpendicular to the ĉ axis—with magnetic field perpendicular or parallel to the ĉ axis—is greater than the mobility parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…As a consequence of the hexagonal structure of SiC, there is a significant anisotropy in the electron mobility between motion of carriers parallel and perpendicular to the c-axis. Anisotropy measurements made on 4H and 6H single crystal SiC show quite different behaviour, with the parallel Hall mobility in 4H material higher than the perpendicular mobility, whereas the opposite case was observed in 6H (Schadt et al 1994). …”
Section: Sic Materials Propertiesmentioning
confidence: 93%
“…As a consequence of the hexagonal structure of SiC, there is a significant anisotropy in the electron mobility between motion of carriers parallel and perpendicular to the c-axis. Anisotropy measurements made on 4H and 6H single crystal SiC show quite different behaviour, with the parallel Hall mobility in 4H material higher than the perpendicular mobility, whereas the opposite case was observed in 6H (Schadt et al 1994). …”
Section: Sic Materials Propertiesmentioning
confidence: 93%
“…The drift carrier mobility in the Al implanted layers of the samples of this study has been obtained as the ratio between the Hall 25 and the measured sheet resistance. The computed curves are shows in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, such effective Hall data can be converted to drift data using the Hall factor curve r H (T) of Ref. 25, as mentioned in the Experimental section. Soon after, it will be shown that the carrier transport in the Al implanted layers of this study features two different mechanisms, one dominant over the other depending on the temperature region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron mobilities parallel and perpendicular to the c-axis show only a weak anisotropy; they differ by less than 25% [1]. Kimoto and co-authors [2] have demonstrated that the electron Hall mobility in nitrogen-doped epilayers ([N] = 1.5 × 10 14 cm -3 ) reaches high values in the range of 950 cm 2 /V s at room temperature.…”
mentioning
confidence: 97%